Puzzle: Songbirds - Allied Products Corporation (Kansas City, MO Allied Materials & Equipment Company, 2015)
This 1000 piece Springbok collection puzzle features a colorful scene of songbirds perched on tree branches.
Keywords: Songbirds -- Puzzle